2009
DOI: 10.1021/ma901624p
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Continuous Porous Organogels, Hydrogels, and Bicontinuous Organo/Hydro Hybrid Gels from Bicontinuous Microemulsions

Abstract: A new class of unique soft gels was produced by gelations of bicontinuous microemulsions (BME). Three alternative composite gel systems, namely BME organogel, hydrogel and an organo/hydro hybrid gel, prepared by hydrogelation and/or organogelation of BME solutions were proposed. These gels were self-supported, and aqueous and oil microphases bicontinuously coexisted and were immobilized in the gels. Even in "one side only" gelation products such as the BME organogel and the BME hydrogel, alternate solvent phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The BME organogels were produced by "rapid" (d and h) and "slow" (e and i) cooling. 27 The structures of BME gels are influenced by the kinetics of the gelation process, rather than by thermodynamic control of the original BME solution structure; this is similar to the case of condensed gels prepared by BME polymerization. Kinetic control of the physical gelation process to produce BME organogels was achieved relatively simply by control of the rate of cooling from the "sol state" to the "gel state".…”
Section: Construction Of Hybrid Soft Materials By Bme Gelationmentioning
confidence: 94%
“…The BME organogels were produced by "rapid" (d and h) and "slow" (e and i) cooling. 27 The structures of BME gels are influenced by the kinetics of the gelation process, rather than by thermodynamic control of the original BME solution structure; this is similar to the case of condensed gels prepared by BME polymerization. Kinetic control of the physical gelation process to produce BME organogels was achieved relatively simply by control of the rate of cooling from the "sol state" to the "gel state".…”
Section: Construction Of Hybrid Soft Materials By Bme Gelationmentioning
confidence: 94%
“…A number of methods for the mesoscale structural control of swollen soft gels, 1 including porous, 28 composite, 3,9 and bicontinuous 35,10a,10b gels, have been proposed and investigated both as soft materials and self-assembly. Among a variety of unique soft gels such as double-network gels, 2 nanocomposite gels, 9 aqua materials, 11 topological gels, 12 hostguest polymer gels, 13 and stimuli-responsive (intelligent) gels 1,10,12a,1315 have seen particular focus because of their potential as polymer materials for actuators 1,13c,14,16 and drug-release systems.…”
mentioning
confidence: 99%
“…17 To form the BME phase, the concentrations of salt and 2-butanol in the system were adjusted (Table S1) 17 according to previous studies. 3 The volumes of separated saline and oil phases in the three-phase solution were equalized to provide a BME sample solution that consisted of equal volumes of saline and toluene on a microscopic scale. The BME solution with NIPAM/MBAAM required a relatively lower salt concentration than the BME solution without monomers, because the monomers existed in the saline phase and decreased the hydrophilicity of the surfactant system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the O/W solution containing the polymers and Cu catalyst was shaken and heated slightly to accelerate the crosslinking reaction before formation of a thin film at the O/W interface and macroscopic separation of the solution, it was found that O/W composite soft gels formed, 20 as shown in Figure 1c. Figures 1d and 1e show typical SEM images of soft gel samples after freeze drying.…”
mentioning
confidence: 99%